Effect of friction stir processing on the high cycle fatigue behavior of AZ31B alloy. (2022) - Sankar, R.; Rathinasuriyan, C.; Vijayan, R.
Abstract: The low-weight metal magnesium alloy finds extensive use in aircraft vehicles, defense vehicles, biomedical, and sporting equipment industries. The friction stir process (FSP), as plastic deformation, has a wide range of influence on mechanical systems and microstructure properties of the material. One of the most essential properties for analysing the failure behaviour of FSP-ed structures is the fatigue life of FSP. The rolling shoulder profile design of the stirring tool with three different cooling mediums was used. This work aims to study the effect of FSP on the fatigue properties of AZ31B alloy under different mediums. Finally, fractographic analysis was performed on different cooling medium samples. The fatigue results show that the SFSP-ed sample has a longer fatigue life compared with the CFSP-ed sample.